Hippocampal subfield volumes are nonspecifically reduced in premature‐born adults. Issue 18 (26th August 2020) - Hedderich, Dennis M.; Avram, Mihai; Menegaux, Aurore; Nuttall, Rachel; Zimmermann, Juliana; Schneider, Sebastian C.; Schmitz‐Koep, Benita; Daamen, Marcel; Scheef, Lukas; Boecker, Henning; Zimmer, Claus; Baumann, Nicole; et al.
Abstract: Reduced global hippocampus volumes have been demonstrated in premature‐born individuals, from newborns to adults; however, it is unknown whether hippocampus subfield (HCSF) volumes are differentially affected by premature birth and how relevant they are for cognitive performance. To address these questions, we investigated magnetic resonance imaging (MRI)‐derived HCSF volumes in very premature‐born adults, and related them with general cognitive performance in adulthood. We assessed 103 very premature‐born (gestational age [GA] <32 weeks and/or birth weight <1, 500 g) and 109 term‐born individuals with cognitive testing and structural MRI at 26 years of age. HCSFs were automatically segmented based on three‐dimensional T1‐ and T2‐weighted sequences and studied both individually and grouped into three functional units, namely hippocampus proper (HP), subicular complex (SC), and dentate gyrus (DG). Cognitive performance was measured using the Wechsler‐Adult‐Intelligence‐Scale (full‐scale intelligence quotient [FS‐IQ]) at 26 years. We observed bilateral volume reductions for almost all HCSF volumes in premature‐born adults and associations with GA and neonatal treatment intensity but not birth weight. Left‐sided HP, SC, and DG volumes were associated with adult FS‐IQ. Furthermore, left DG volume was a mediator of the association between GA and adult FS‐IQ in premature‐born individuals. Results demonstrate nonspecifically reduced HCSF volumes in premature‐born adults; but specific associations with cognitive outcome highlight the importance of the left DG. Data suggest that specific interventions toward hippocampus function might be promising to lower adverse cognitive effects of prematurity. Abstract : Hedderich et al. report unspecific reductions of hippocampus subfield volumes in premature‐born adults. However, they found reduced dentate gyrus volumes to mediate the effect of low gestational age on adult full‐scale intelligence quotient suggesting functional relevance in premature‐born adults.